PERBANDINGAN ANTARA KETEGUHAN REKAT LEM PUTIH DENGAN LEM KUNING PADA KARPET KAYU - Sigit Baktya Prabawa (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
Wooden carpets are one of the products made of woody materials glued on the textiles. The wooden part can be in the form of plywood or solid wood, while the textiles as a carpet backing serves as a link between the pieces of woody material that make up the carpet. Compared to fabric carpets, wood carpets have several advantages in terms of health and maintenance. Wood carpet generally include woody material, fabrics, glue and finishing materials. The glue serves as an adhesive between woody material and fabric. The shear strength of glue adhesives has an important role in wood carpet products. In the local market there are several types of glue such as white glue (Polyvinyl Acetate) and yellow glue (Synthetic Rubber). The purpose of this study was to compare the shear strength of white and yellow glue. It is expected that people can choose the type of glue that is more suitable for wood carpets. The research data was tabulated and analysed by paired t-test. The results showed that the shear strength of white and yellow glue using manual clamps were 27.95 kg cm-2 and 13.78 kg cm-2 respectively. The shear strength of white glue strongly differ with those of yellow glue, and greather two times than the yellow one. In making or producing wooden carpets, it is recommanded to use white glue instead of yellow one and can apply manual clamps. However, for better results, it is recommended to apply a press machine.